MENGINTEGRASIKAN PLATFORM MAKRO-SOSIAL DAN PRAKTIK KERJA UNTUK MANAJEMEN PERGURUAN TINGGI DALAM MENGHADAPI ERA DISRUPTION - Mustain, Mustain (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Higher education is held on the basis of the spirit of discovery to orient its activities to be able to achieve great "discoveries" that are useful for changes in human life in the future. This macro-social platform raises a new paradox, to express opinions and creativity tend to be regarded as mere products, so that in higher education, the prevailing consensus is that we do not really face the same changes faced by business. Because the substantial dependence of various systems and actors in developing and implementing innovative solutions involves renegotiating tertiary institutions in a progressive or renewal manner. The purpose of this paper is to describe Integrating macro-social platforms and work practices for management of universities in the face of era disruption. The results of the discussion concluded: 1) Management of teaching and learning must be project-based in a tangible manner by utilizing an interdisciplinary and problem-based approach through collaboration with industrial and academic partners. 2) Supporting student autonomy requires support in managing their learning transitions by requiring (i) empathy awareness of the fact that individuals learn differently (ii) clarifying with students that cognitive styles are as important as their learning abilities to support them in developing attention more adaptive; (iii) support students' basic psychological needs related to intrinsic motivation to increase satisfaction and adoption of a deeper approach to learning; (iv) supporting students to develop different / more appropriate terms of reference for new learning environments; (v) work with students to increase cognitive flexibility; (vi) ensuring coherent program design; (vii) explicit introduction, and induction into the requirements of the new learning environment and the objectives of specific learning activities. 3) The aim of higher education is to equip students with the skills they need to succeed in the world of work and to make an impact on the world in general by avoiding traditional lectures and textbooks for project-based learning activities where students work in teams to solve problems without solutions clear. 4) Today's demands for higher education managers are greater than before. Effectiveness as a college leader requires managers to master four important prerequisites. They must know their environment, know their university, know their department and know themselves as individuals. 5) understanding the company creating wealth through labor investment can be complicated and a line of sight to assess company-level results is not always direct. However, developing such an understanding is key for practitioners and academics.